The sorcerer's apprentice - Turteltaub, Jon.; Bruckheimer, Jerry; Baruchel, Jay, 1982-; Bellucci, Monica, 1968-; Cage, Nicolas, 1965-; Palmer, Teresa, 1986-; Molina, Alfred, 1953-; Konner, Lawrence; Rosenthal, Mark D.; Lopez, Matt.; Miro, Doug.; Bernard, Carlo; et al. (Burbank, Calif. : Disney : Distributed by Buena Vista Home Entertainment, 2010)
Balthazar Blake is a modern-day sorcerer with his hands full defending Manhattan against dark forces. When a seemingly average kid shows hidden potential, Balthazar takes his reluctant recruit on a crash course in the art and science of magic to become the ultimate sorcerer's apprentice.
Widescreen.
Bonus features: The making of The sorcerer's apprentice; delted scene: Balthazar recruits Dave.
Director of photography, Bojan Bazelli ; editor, William Goldenberg ; music, Trevor Rabin.
Jay Baruchel, Monica Bellucci, Nicolas Cage, Teresa Palmer, Alfred Molina.
MPAA rating: PG; for fantasy action violence, some mild rude humor and brief language.
DVD ; Dolby digital 5.1 surround (English, French and Spanish) and DVS 2.0 stereo. (English).
Keywords: Wizards -- Drama; Apprentices -- Drama; Magic -- Drama; Manhattan (New York, N.Y.) -- Drama; Action and adventure films; Films for the hearing impaired; Films for people with visual disabilities; Feature films; Fantasy films